Middle Dutch back vowels in rhymes - Sytsema, J; Grijzenhout, J; Lahiri, A (Springer Netherlands, 2014)
Dutch underwent many changes in its vowel system in the course of its history. One way of exploring the phonology of the vocalic system at an earlier period of the language is to examine rhymes. The rhyming verse which is used in the moral didactic text of Ms. Marshall 29 offered an excellent opportunity to not only establish the differences between Modern and Middle Dutch, but also to trace any variation in the transition period from early to late Middle Dutch. We focused on rounded vowels, which were indicated by seven graphemes: , <uu>, <uy>, <ue>, <oo>, <oe>, and <o>. Our crucial findings are the following: (i) descendants of Proto Germanic (PGmc) */au/ and */o:/ never rhyme with each other, although they could be spelt in an identical fashion and are pronounced the same in Modern Dutch, which leads us to conclude that the Middle Dutch vowel qualities were different; (ii) descendants of PGmc */u/ became /ɔ/, but when this vowel is lengthened in open syllables, it never rhymes with vowels derived from PGmc */au/, although they do in Modern Dutch; (iii) although <e> added to a vowel can mark length, in a small subset it must have indicated fronting.